The value of reviving the urban identity of Downtown Kulim, Kedah - Alamah Misni,; Siti Anis Nadia Aziz, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Urban identity can be defined as an interaction with places, where people describe themselves in terms of belonging to a specific place. In this study, reviving the identity and image of Downtown Kulim was identified with making it authentic by enhancing its local physical characters which emphasize on the function of open spaces, systematic street linkages and conservation of historic features. The primary data which were gathered through field observations and recording were synthesized to determine the potential segments to be developed and preserved. The design ideas of physical transformation and of creating open spaces were inspired by "The history of Pattani architecture, community and culture". The spaces were designed to be more functional, systematic street linkages, incorporating conservation of historic features. These strategies were to make the place retain its authentic local identity in facing the 2020 modernism. Bringing back the nostalgic value, meaning and identity of Downtown Kulim as the first starting settlement of the Malay, Pattani era would give it an excellent and memorable experiential journey.